Perceived organizational support and kindergarten teachers’ voice behavior: the mediating role of psychological capital and the moderating role of establishment status - Gou, Yu; Zeng, Gang; Xu, Ying; Xie, Xiao (Frontiers in Psychology, 2025)
Perceived organizational support is associated with employee voice behavior; however, existing research has paid little attention to the interplay between organizational and individual factors and the mechanisms through which they influence employee voice behavior. This study employed a questionnaire survey method, collecting data from 314 preschool teachers. The collected data were analyzed using Amos 27.0 and SPSS 27.0 statistical software. Additionally, the moderating effect of establishment status on the relationship between teachers’ perceived organizational support and psychological capital was not significant, providing theoretical insights for future research on kindergarten teachers.